Towards a monophyletic classification of Lejeuneaceae II: subtribes Pycnolejeuneinae and Xylolejeuneinae subtr. nov., transfer of Otolejeunea to Lepidolejeuninae, and generic refinements - Heinrichs, Jochen; Dong, Shanshan; Schäfer-Verwimp, Alfons; Peralta, Denilson F.; Feldberg, Kathrin; Schmidt, Alexander R.; Schneider, Harald (Phytotaxa, 2014)
Lejeuneaceae are the most species rich family of leafy liverworts and arguably the most difficult group in terms of generic delimitation. Although much progress has been made in recent years, the generic classification of Lejeuneaceae has not yet been satisfactorily solved. Here, we present phylogenetic analyses of a three marker dataset (nrITS, cp DNA rbcL and trnL-trnF) derived from 113 accessions of Lejeuneeae and 13 outgroup species. Based on maximum parsimony analyses and Bayesian inference of phylogeny, we propose the new subtribes Pycnolejeuneinae and Xylolejeuneinae, reinstate the genera Cystolejeunea and Cyrtolejeunea, and transfer Otolejeunea from Cyclolejeuneinae to Lepidolejeuneinae.